Síndrome de superposición: hepatitis autoinmune y colangitis biliar primaria. Resultados a largo plazo de una cohorte retrospectiva en un hospital universitario (2018)
ABSTRACT: Background Autoimmune hepatitis (AIH) with characteristics of primary biliary cholangitis (PBC) is known as overlap syndrome. Its prevalence and prognosis have not yet been determined comparatively with AIH. Methods A retrospective cohort study was conducted comparing patients diagnosed with AIH and AIH-PBC overlap syndrome, followed-up for seven years in a university hospital in Colombia, until 31 December 2016. Results A total of 210 patients were included (195 women, mean age 48.5 years). Of these, 32 (15.2%) had AIH-PBC overlap syndrome. At diagnosis, no significant differences were found by demographic profile, positive autoantibodies (ANA, ASMA), except AMA (81.2% vs 3.9%, P < .001), and histological grade of fibrosis. The most frequent clinical presentations were nonspecific symptoms in AIH-PBC and acute hepatitis in AIH. Although there were no significant differences, AIH showed a greater biochemical response to immunosuppressive management (87.3% vs 74.2%, P = .061) and a greater number of relapses in those who achieved partial or complete remission during treatment (12.4% vs 7.63%; P = .727). Patients with AIH-PBC had greater progression to cirrhosis (22.2% vs 13.1%, P = .038), even in those who achieved partial or complete biochemical remission without relapse, with greater indication of orthotopic liver transplantation (P = .009), but not retransplantation (P = .183); there were no differences in mortality. Conclusions AIH-PBC overlap syndrome accounts for a significant proportion of patients with AIH, with greater progression to cirrhosis, indication of liver transplantation and possibly retransplantation. This higher risk of adverse outcomes suggests closer monitoring, probably with follow-up until confirmed histopathological remission.